2016
DOI: 10.1039/c5np00153f
|View full text |Cite
|
Sign up to set email alerts
|

I only have eye for ewe: the discovery of cyclopamine and development of Hedgehog pathway-targeting drugs

Abstract: During the 1950s, sheep ranchers in the western United States experienced episodic outbreaks of cyclopic lambs. In this highlight I describe how these mysterious incidents were traced to the grazing of Veratrum californicum wildflowers by pregnant ewes, leading to the discovery of cyclopamine (1) as a plant-derived teratogen. The precise mechanism of cyclopamine action remained enigmatic for 30 years, until this steroid alkaloid was found to be the first specific inhibitor of Hedgehog (Hh) signalling and a dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 45 publications
0
40
0
1
Order By: Relevance
“…In vitro imaging revealed that this protein was more abundant towards the centre compared with the peripheral layers (Figure L–N). These cells were then cultured in medium containing a hedgehog inhibitor, cyclopamine, which is known to induce severe bone malformations (Chen, ). Compared to the vehicle treated samples (Figure O), lower concentrations (10 and 20 μ m ) delayed self‐aggregation (data not shown); a higher concentration (100 μ m ) prevented it entirely (Figure P).…”
Section: Resultsmentioning
confidence: 99%
“…In vitro imaging revealed that this protein was more abundant towards the centre compared with the peripheral layers (Figure L–N). These cells were then cultured in medium containing a hedgehog inhibitor, cyclopamine, which is known to induce severe bone malformations (Chen, ). Compared to the vehicle treated samples (Figure O), lower concentrations (10 and 20 μ m ) delayed self‐aggregation (data not shown); a higher concentration (100 μ m ) prevented it entirely (Figure P).…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, vismodegib is part of a larger class of compounds that inhibit Hh signaling by binding to the transmembrane protein Smoothened (Robarge et al, 2009; Chen et al, 2002; Keeler, 1975; Chen, 2016). With both synthetic and natural small molecules, this group includes more than 20 compounds and continues to grow, with increasing attention focused on the biological effects of Hh-pathway inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…The first such molecule discovered is the naturally occurring teratogen and SMO antagonist, cyclopamine (Chen, 2016). Human exposure to naturally occurring or synthetic SMO inhibitors may therefore be a risk factor for HPE.…”
Section: Gene-environment Interactions In Hpementioning
confidence: 99%